The effect of flush feeding during lactation on sow reproductive efficiency, litter size, birth weight and within litter variation - Webb, E.C. (Edward Cottington) (University of Pretoria, 2021)
Dissertation (MSc (Agric) Animal Science: Production Physiology and Product Quality)--University of Pretoria, 2021.